Analisis Flypaper Effect Belanja Pemerintah Daerah Di Indonesia Berbasis Vector Autoregressive (VAR) - Heryana, Toni (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2014)
Regional autonomy as local independence acceleration policy framework still has not managed to demonstrate achievement, especially in the fiscal aspects. Start from these problems, this research aims: first, examines the relationship between the General Allocation Fund (Dana Alokasi Umum, DAU) and expenditure area consisting of operating expenditure and capital expenditure; the second examines the relationship between revenue local own (Pendapatan Asli Daerah, PAD) and the expenditure area consisting of operating expenditures and expenditures capital. Third, it examines the relationship DAU and PAD; Fourth, it examines whether there is a flypaper on capital expenditure and operating expenditure regency/ cities in Indonesia during the period 2004 to 2013. In line with these objectives in research analysis tool used is the Granger Causality Test and Vector Autoregressive (VAR). The results show: first, DAU and operating expenditures do not have a reciprocal relationship, while the capital expenditure, DAU has a reciprocal relationship with the capital expenditure. Second, revenue and operating expenditures have a reciprocal relationship, so did his relationship with capital expenditure. Third, DAU and PAD do not have a reciprocal relationship, even though it is actually contrary to the practice that occurs in a government in which the determination of the amount of DAU is based on the PAD. Fourth, there is a flypaper in relation DAU, PAD with capital expenditure.